The Effect of Media Attention, Institutional Ownership and Political Connection on Tax Avoidance - Melati, Adinda; Prasidya, Tusta Citta Ihtisan Tri (SIMAK, 2025)
The purpose of this study was to analyze the effect of media attention, institutional ownership and political connections on tax avoidance in State-Owned Enterprises (SOEs) companies. The population of this study is state-owned companies that will be listed on the Indonesia Stock Exchange during 2021-2023. During 2021-2023, 36 companies were used as research samples. The research approach used is a quantitative approach with multiple regression analysis. This research uses testing using the SPSS 25 statistical tool. This research technique uses purposive sampling in sample selection. The results found that institutional ownership has a significant effect on tax avoidance, political connections have a significant effect on tax avoidance, media attention has no significant effect on tax avoidance.